DAI SELAIN NABI DALAM AL-QUR’AN - Akhmad Nizaruddin (Universitas Islam Depok, 2022)
Da'wah is an obligation that Allah imposes on every Muslim according to his ability. In the Qur'an, it is narrated that the da'i who carried out the mandate of da'wah came from among the prophets and from other than the prophet. This study aims to explain the figures of preachers from groups other than the prophets that Allah describes in the Qur'an. In this study, the writer uses library research by collecting verses that describe the preachers other than the prophet and the explanations of the commentators on these verses. From this research, the author found eleven figures or preachers from other than prophets and apostles whom Allah has immortalized in the Qur'an, namely Thalut, the preacher who reminded Ashab sabt, Ashhabul Kahf, the preacher who invited the owner of two gardens, Zulqarnain, the preacher who gave warning to Prophet Musa, the preacher who reminiscent of treasure, Lukman Al Hakim, dai in surah Yasin, dai from the Pharaoh's family, and from the jinn.